Measuring, Modeling and Simulating the Re-adaptation Process of the Human Visual System after Short-Time Glares in Traffic Scenarios - Meyer, Benjamin; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2017)
Benjamin Meyer performs several psycho-physical experiments to measure the re-adaptation process of glared drivers in traffic scenarios. The author then develops a novel tone mapping algorithm to simulate the recurring contrast perception of the human eye by adjusting the displayed contrast. Depending on background illumination, bright light sources cause considerable perception restrictions for a glared viewer and can deter the driver from perceiving critical objects for several seconds and severely increase the risk of accidents. Based on the results of the conducted user studies, this vision impairment is integrated into a night driving simulator. The modified driving simulation provides a more realistic visualization and enables the analysis of critical traffic scenarios including short-time headlight glares. This leads to better transferability of driving simulator results and enables investigating driving behavior in the presence of glare. Contents Measuring Contrast Perception User Studies and Field Test Modeling, Simulation, and Evaluation Target Groups Researchers, Students, and Practitioners in the Field of Computer Science, Computer Graphics, Cognitive Psychology and Automotive Engineering About the Author Dr. Benjamin Meyer studied computer science from 2003 to 2008 with specialization in computer graphics. After his graduation, he worked five years as a research associate at a computer graphics lab, where this thesis was developed as a joint work with a major German car manufacturer.
Measuring Contrast Perception -- User Studies and Field Test -- Modeling, Simulation, and Evaluation.
Keywords: Computer graphics; Computer simulation; User interfaces (Computer systems).; Human-computer interaction; Cognitive psychology; Computer Graphics; Computer Modelling; User Interfaces and Human Computer Interaction; Cognitive Psychology